2011
DOI: 10.4049/jimmunol.1003093
|View full text |Cite
|
Sign up to set email alerts
|

Absence of MyD88 Results in Enhanced TLR3-Dependent Phosphorylation of IRF3 and Increased IFN-β and RANTES Production

Abstract: Toll-like receptors are a group of pattern-recognition receptors that play a crucial role in “danger” recognition and induction of the innate immune response against bacterial and viral infections. TLR3 has emerged as a key sensor of viral dsRNA, resulting in the induction of the anti-viral molecule, IFN-β. Thus, a clearer understanding of the biological processes that modulate TLR3 signaling is essential. Previous studies have shown that the TLR adaptor, Mal/TIRAP, an activator of TLR4, inhibits TLR3-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 39 publications
(42 reference statements)
4
67
1
Order By: Relevance
“…It has been found that in mammals MyD88 interacts directly with several IRFs including IRF1, IRF4, IRF5, and IRF7 (28,29,33,34). An initial study has suggested that human MyD88 does not interact with IRF3 (9); however, later research demonstrated that murine MyD88 does interact with IRF3 (35). Unlike MyD88, whose amino acid sequence is relatively well conserved, the sequences of the IRFs have diverged to a much greater extent throughout the vertebrate evolution (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that in mammals MyD88 interacts directly with several IRFs including IRF1, IRF4, IRF5, and IRF7 (28,29,33,34). An initial study has suggested that human MyD88 does not interact with IRF3 (9); however, later research demonstrated that murine MyD88 does interact with IRF3 (35). Unlike MyD88, whose amino acid sequence is relatively well conserved, the sequences of the IRFs have diverged to a much greater extent throughout the vertebrate evolution (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, signals derived from fibroblasts such as IL-1-dependent induction of IL-6, GM-CSF, or keratinocyte growth factor (KGF) [51,52], or T-cell-dependent production of IL-22 [53] or IL-31 [54] might be indirectly involved in keratinocyte proliferation after OVA sensitization. Since MyD88 deficiency enhances TRIF-induced signaling [55], it might be possible that this would lead to enhanced IFN-b production. TRIF signaling limits skin barrier dysfunction in a model of aspergillusinduced eczema in mice [56].…”
Section: Discussionmentioning
confidence: 99%
“…HEK293, HEK293-TLR3, HEK293-TLR4, and HEK293-TLR9 cells (5 3 10 4 cells/well; 96-well plate) were transfected with 80 ng/well luciferase reporter gene plasmid for NF-kB and IFN-b and cotransfected with the expression vectors encoding ADAM15, TRIF, MyD88, and MDA5, as indicated, using lipofectamine, as previously described (8). A total of 40 ng/well phRL-TK (TK-Renilla-luciferase) reporter gene was cotransfected simultaneously to normalize data for transfection efficiency.…”
Section: Reporter Gene Assaysmentioning
confidence: 99%
“…The IRF3/7 dimers then translocate to the nucleus, in association with transcriptional coactivators, such as CBP and p300, and bind to target sequences in DNA, such as IFN-stimulated response elements (8,9). Also, the IRFs, together with the transcription factors ATF-2/c-Jun and NF-kB from the IFN-b enhanceosome, bind to a nucleosome-free enhancer region within the IFN-b promoter upstream of the transcription start site, leading to transcriptional activation of the IFN-b gene (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation